The Specific Capacitive Performances of the Manganese Oxyhydroxide/Carbon microcoil Electrodes for Supercapacitors. (1st January 2015) - Wang, Tao; Zhu, Yabo; Xing, Zheng; Tang, Guoxia; Fan, Heliang
Highlights: MnOOH@carbon microcoil composites are successfully prepared. The pseudo-capacitive behaviors are extensively studied. The composites show good electrochemical performance. Energy storge mechanism of the electrode material is discussed. Abstract: Manganese oxyhydroxide (MnOOH)/carbon microcoil (CMC) composites are fabricated by micro-wave deposition. Then, their structures are characterized by scanning, transmission electron microscopy and X-ray diffraction. This work presents an extensive study of the pseudocapacitive performances of the as−prepared MnOOH@CMC electrodes in mild Na2 SO4 electrolyte. It shows a specific capacitance of 396 F g −1 at a scan rate of 2 mV s −1 . Moreover, these binary composites exhibit a good rate capability and cycling stability, retaining 137.6 F g −1 at current density of 2 A g −1 after 10, 000 cycles. The good electrochemical performances of the composites are attributed to the ions from the electrolyte can easily diffusing into almost all pores of the electrode, leading to a complete insertion reaction.